Vstavitev subduro-peritonealne drenaže pri bolniku s ponavljajočim se obojestranskim subduralnim higromom - Ravnik, Janez (Zdravniški vestnik, 2007)
Subdural hygroma is collection of the cerebrospinal-like fluid in the subduralspace. It is usually asymptomatic. Sometimes gradual increase is notedwhich acts tensionally and causes pressure on the brain structures. It this case surgical treatment is necessary which is usually straightforward. Inthe paper a case of a patient is presented where after craniocerebral injurybilateral symptomatic subdural hygroma developed. He was first treated with insertion of bilateral subdural drainage and then with repeated subdural taps. After both therapeutic measures the hygroma always recurred with worsening of the clinical condition. For permanent resolution of the hygroma an insertion of the subduro peritoneal drainage was needed. After this operation the patientfully recovered. Two months after the operation he is without problems and the hygroma did not recur This case report proves that inrecurrent subdural hygroma insertion of the subdurotoneal drainage is a goodtreatment option. Unilateral drainage could be beneficial even in bilateral hygroma.
Keywords: Complications; drenaža; Head Injuries; Middle Age; neurology; nevrologija; Ponovitev; Recurrence; Srednja leta; Subdural Effusion; Subdural Space; Subduralni izliv; Subduralni prostor; therapy; Tomografija radiografska, računalniška; Tomography, X-Ray Computed; zdravljenje